(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sugiharto S, Atmaja BM, Widiastuti E, Hadiyanto H. 2021. Combined use of Spirulina platensis and Saccharomyces cerevisiae: Implication on growth, blood profile and intestinal morphology and bacteria of the Indonesian crossbred chickens. Biodiversitas 23: 160-165. The effects of Spirulina platensis and Saccharomyces cerevisiae on poultry growth and health have long been known. However, no research has been conducted on the combined use of these substances on the Indonesian crossbred chicken (ICC). This study evaluated how the combined use of S. platensis and S. cerevisiae affected ICC growth, blood profile, and intestinal ecology. A total of 288 ICC were separated into three groups, including CONT (basic diet), SP (diet with 0.3% S. platensis), and SPSC (diet with 0.3% S. platensis and 0.2% S. cerevisiae). Blood and intestinal content and segments were taken at week 9, while growth was determined weekly. SP had greater (p<0.05) body weight than CONT, but did not differ from SPSC. In SP, ileal coliform counts were lower (p=0.07) than in CONT. SPSC had lower (p=0.07) caecal Enterobacteriaceae counts than other groups. Blood profile, intestinal morphology, organ weight, and carcass traits did not vary (p>0.05) across the ICC. In conclusion, dietary supplementation of S. platensis improved growth performance and bacterial population of the ICC.